Implementation of Waste Management Policy In Public Services at the Poso District Environmental Service - Mohammad Rusli Syuaib (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The purpose of this study is to analyze the implementation of waste management policies in public services at the Poso Regency Environmental Service seen from the dimensions of communication, resources, dispositions and bureaucratic structure, and factors that hinder the implementation of waste management policies in public services at the Poso Regency Environmental Service. The data for this study came from two sources: primary data, which were collected directly through observation and interviews, and secondary data, which were in the form of papers from organizations involved in the study. In this study using descriptive analysis, the results obtained were that the implementation of waste management policies in providing public services at the Poso Regency Environmental Service was very good because it was supported by four dimensions of implementation, and the main obstacle found in the implementation of waste management policies in providing public services at the Poso Regency Environmental Service was the limited physical facilities and infrastructure used in the implementation of waste management policies in providing public services at the Poso Regency Environmental Service.